Solubilization of Vitamin E in culture medium and its antioxidant activity - Jaswir, Irwandi; Sahul Hamid, Siti Fairus (IIUM Press, 2011)
In this project. was developed a solubilization method of vitamin E in DMEM (Dulbecco modified Eagle's minimal essential medium) cullure medium in order to anain lIigher concentration abwrbance of vitamin E. TIterI' are two method which are conventional and evaporation methods. Vitamin E plays an important role in prevention of chronic disease. Furthermore. we will compart and contrruil com'entional and evaporation melhod for solubilizalion of vitamin E in cullure medium. Cellular uptake. antioxidative as well as possible prooxidam activilies of l'iTamin E in DMEM medium was determined under a wide range oflheir concemration, The aspeci thai concerol'd in Ibis project is the optimum process condition 10 yield Ihe highcst concentrations of vil3min E. The process conditions in tbis proje<:t are the concemration ofTetrahydrofuran (THf) and concentration of "ilamin E where the function ofTIif is to enhance the solubilization. The Desib'Il Expert software with Central Composite Design was used in Ihis project for the optimization purpose and analyzes the antioxidant activity. Evaporation performed the best method compare to th" corwentional method dill' to the higher antioxidant activily. The percentage IS 97.5'10 when lls.e 6O...M and 6%of THF